2020
DOI: 10.3389/fphys.2020.00063
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Alternatives in the Treatment of Amyotrophic Lateral Sclerosis: A Comprehensive Review

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that produces a selective loss of the motor neurons of the spinal cord, brain stem and motor cortex. Oxidative stress (OS) associated with mitochondrial dysfunction and the deterioration of the electron transport chain has been shown to be a factor that contributes to neurodegeneration and plays a potential role in the pathogenesis of ALS. The regions of the central nervous system affected have high levels of reactive oxygen species (ROS) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 537 publications
(620 reference statements)
1
60
0
1
Order By: Relevance
“…As previously mentioned, ROS are produced by mitochondria both in physiological and pathological conditions [149] and can be responsible for onset and progression of many neurodegenerative diseases [150,151]. Furthermore, as discussed above, one of the major events related to neurodegenerative diseases, driven by the redox status, is microglial activation-derived neuroinflammation [152]: the induction of the expression of proinflammatory genes leading to the release of cytokines and chemokines can represent a consequence of the uncontrolled ROS production by mitochondria.…”
Section: Antioxidantmentioning
confidence: 98%
See 4 more Smart Citations
“…As previously mentioned, ROS are produced by mitochondria both in physiological and pathological conditions [149] and can be responsible for onset and progression of many neurodegenerative diseases [150,151]. Furthermore, as discussed above, one of the major events related to neurodegenerative diseases, driven by the redox status, is microglial activation-derived neuroinflammation [152]: the induction of the expression of proinflammatory genes leading to the release of cytokines and chemokines can represent a consequence of the uncontrolled ROS production by mitochondria.…”
Section: Antioxidantmentioning
confidence: 98%
“…Finally, as reviewed by Reiter et al [176], melatonin is able to counteract oxidative stress not only directly interacting with free radicals [177], but also by stimulating antioxidant enzymes and upregulating GSH synthesis, through an indirect pathway. For these reasons, its use in the treatment of neurodegenerative diseases has been proposed: in vitro it exerted an antiapoptotic activity and in vivo it improved behavioral and cognitive functions and extended the lifespan of AD and ALS mice and rats [151,[178][179][180][181]; furthermore, it enhanced locomotor performances in PD mouse models [182]. Otherwise, meta-analysis and clinical trials on AD and PD patients revealed only an improvement in sleep quality without any ameliorations in terms of cognitive or motor functions and clinical trials testing melatonin in a specific range dose to establish its neuroprotective activity are needed [181][182][183].…”
Section: Synthetic Antioxidantsmentioning
confidence: 99%
See 3 more Smart Citations